2002
DOI: 10.3727/000000002783992433
|View full text |Cite
|
Sign up to set email alerts
|

αNAC Requires an Interaction With c-Jun to Exert its Transcriptional Coactivation

Abstract: αNAC is a transcriptional coactivator known to interact with the N-terminal activation domain of the c-Jun transcription factor. In this article, we describe the identification of the c-Jun interaction domain within the αNAC protein. Deletion analysis of αNAC indicated that the c-Jun binding site was located in the middle part of the protein, between residues 89 and 129. The deletion of the C-terminal end of αNAC, including the c-Jun interacting domain, induced a nuclear translocation of the mutated coactivato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 27 publications
(11 reference statements)
0
22
0
Order By: Relevance
“…However, the possibility cannot be excluded that this mechanism is involved in the cytosolic retention of other factors important for erythroid cell maturation. NACA is also known as a coactivator of c-JUN-mediated transcription in developing bone during embryogenesis Quelo et al, 2002). However, because c-JUN behaves as a negative regulator of erythropoiesis (Elagib et al, 2004), the positive effect of NACA on erythroid-cell maturation cannot be explained by its c-JUN-mediated positive contribution.…”
Section: Discussionmentioning
confidence: 99%
“…However, the possibility cannot be excluded that this mechanism is involved in the cytosolic retention of other factors important for erythroid cell maturation. NACA is also known as a coactivator of c-JUN-mediated transcription in developing bone during embryogenesis Quelo et al, 2002). However, because c-JUN behaves as a negative regulator of erythropoiesis (Elagib et al, 2004), the positive effect of NACA on erythroid-cell maturation cannot be explained by its c-JUN-mediated positive contribution.…”
Section: Discussionmentioning
confidence: 99%
“…We have engineered a series of C-terminal and internal deletion mutants of the ␣NAC protein (37,38) and tested them for DNA-binding activity with EMSA (data not shown). …”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that ␣NAC functions as a c-Jun coactivator (30,(36)(37)(38). The cloning of ␣NAC as a differentially expressed gene product in terminally differentiated osteoblasts (47) and the expression of the ␣NAC protein in mineralizing osteoblasts at the ossification centers of developing embryos (30) suggested that ␣NAC should be involved in some aspects of the regulation of gene transcription in differentiated bone-forming cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CREB then stimulates the transcription of members of genes coding for the AP-1 family of basic domain- leucine zipper transcription factors, c-Fos and c-Jun (38)(39)(40). While the importance of AP-1 proteins in mediating the anabolic PTH response remains to be determined, it is noteworthy that ␣NAC interacts with the N-terminal activation domain of c-JUN to regulate transcription (16,20,21,41). Interaction with c-JUN involves residues 89 to 129 within ␣NAC (41), a region containing 5 ␤-sheets (42).…”
Section: Discussionmentioning
confidence: 99%